2003
DOI: 10.1117/1.1560011
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of in vivo photosensitizer fluorescence and photodynamic-therapy-induced depth of necrosis in a murine tumor model

Abstract: We compared light-induced fluorescence (LIF) to nominal injected drug dose for predicting the depth of necrosis response to photodynamic therapy (PDT) in a murine tumor model. Mice were implanted with radiation-induced fibrosarcoma (RIF) and were injected with 0, 5, or 10 mg/kg Photofrin. 630-nm light (30 J/cm(2), 75 mW/cm(2)) was delivered to the tumor after 24 hours. Fluorescence emission (lambda(excitation)=545 nm, lambda( emission)=628 nm) from the tumor was measured. The LIF data had less scatter than inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 20 publications
0
23
0
6
Order By: Relevance
“…2 and 4 show that there is a clear correlation between the measured quantities, indicating that deeper necrosis is achieved for larger decrease in the PS surface fluorescence. A previous study has been published by Cheung et al 23 presenting in vivo correlation of the PS fluorescence and the depth of necrosis. That study, however, is different from the present one, because in their case fluorescence was only measured before illumination as a way to quantify the amount of drug present in the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 4 show that there is a clear correlation between the measured quantities, indicating that deeper necrosis is achieved for larger decrease in the PS surface fluorescence. A previous study has been published by Cheung et al 23 presenting in vivo correlation of the PS fluorescence and the depth of necrosis. That study, however, is different from the present one, because in their case fluorescence was only measured before illumination as a way to quantify the amount of drug present in the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported water concentration in tissue using near-infrared spectroscopy in the spectral range of 700 to 1100 nm (21,34,53). Photofrin concentration is easily extracted using fluorescence techniques (54), which are of interest, but not used in this study.…”
Section: Oxygen Measurement and Photodynamic Therapy Outcomementioning
confidence: 99%
“…Although Ps-PDT is no longer a first-line endoscopic treatment at our institution, we continue to work for improved treatment results by using Ps-PDT with optimized laser light dosimetry by measuring the light absorption and scattering properties of esophageal tissue and the actual drug levels and oxygen content in the mucosa in addition to the thickness of the esophageal wall. [43][44][45][46] The strength of our study is the comparison of large cohorts of patients treated with 3 different endoscopic treatments for BE neoplasia at the same center. The use of a comprehensive BE database included patients with all www.giejournal.org Volume -, No.…”
Section: Discussionmentioning
confidence: 99%